Extraction of Kurarinone and Leachianone A from Sophora flavescens Ait using Ultrasonic Wave - Jin, Y.; Kim, Y.S.; Cheng, Y.D.; Lee, K.J. (Asian Journal of Chemistry, 2012)
Sophora flavescens Ait (Leguminosae) is a Chinese herbal medicine. Sophorae radix, the dried roots of S. flavescens, has been used for various diseases including atherosclerosis and arrhythmias. For the extraction of the kurarinone and leachianone A from Sophorae radix, different ultrasonic waves (40, 72 KHz) and extraction time (30, 60 min) were used with different extraction solvents such as water and ethanol. The extracted samples were analyzed by reversedphase high performance liquid chromatography coupled with mass spectroscopy (RP-HPLCMS). In HPLC condition, the mobile phase applied was linearly changed with A/B of 80/20-65/ 35 vol. % for 60 min (A: water/acetic acid, 99.9/0.1 vol. %, B: acetonitrile/acetic acid, 99.9/0.1 vol. %). From the experimental results, the highest yield of extraction amount 6.025 g was obtained by ultrasonic waves with a frequency of 72 KHz and an extraction time of 30 min. When the pre-irradiated time was increasing, the kurarinone and leachianone A yields decreased. This work would be useful for chemical and biological studies of S. flavescens Ait and its products.